Effect of salinity on growth of the green alga Caulerpa sertularioides (Bryopsidales, Chlorophyta) under laboratory conditions - Mosquera-Murillo, Zuleyma; Peña-Salamanca, Enrique Javier (HIDROBIOLÓGICA, 2016)
Background. Salinity, temperature, nutrients, and light are considered essential parameters to explain growth and distribution of macroalgal assemblages in coastal zones. Goals. In order to evaluate the effect of salinity on the growth properties of Caulerpa sertularioides, we conducted this study under laboratory conditions to find out how salinity affects the distribution of this species in coastal tropical environments. Methods. Five ranges of salinity were used for the experiments (15, 20, 25, 30, and 35 ppt), simulating in situ salinity conditions on the south Pacific Coast of Colombia. The culture was grown in an environmental chamber with controlled temperature and illumination, and a 12:12 photoperiod. The following growth variables were measured weekly: wet biomass, stolon length (cm), number of new fronds and rhizomes. In the experimental cultures, growth (increase in wet biomass and stolon length) was calculated as the relative growth rate (RGR), expressed as a percentage of daily growth. Results. Significant differences (p <0.001) were found between 15 ppt and the remaining treatments (20, 25, 30, and 35 ppt). The highest growth rates were recorded at 25 ppt (4.82 % d-1), while at 15 ppt, whitening and progressive deterioration of C. sertularioides fragments were observed. These results are consistent with the natural habitat of C. sertularioides in Tumaco Bay (Nariño, Colombia), where it is found in areas with average salinities of 24 ppt during its annual cycle. Conclusions. The physiological responses obtained in this study will be valuable in exploring possible effects of environmental conditions on the growth and distribution of Caulerpa in tropical estuaries.